Notes on the collection of fungus gnats left by the late Prof. Galina Petrovna Ostroverkhova with a new specific synonymy in the genus Mycetophila Meigen (Diptera: Mycetophilidae) - Subbotina, Elena; Kurina, Olavi (Zootaxa, 2012)
The late Professor Galina Petrovna Ostroverkhova (née Plotnikova; 1935–2008), of Tomsk State University in Russia, a specialist in Sciaroidea, studied mostly the Siberian fauna of that diverse group of Diptera. She published altogether 52 papers devoted to fungus gnat taxonomy and ecology (for complete list see Babenko & Shcherbakov 2010). The most comprehensive publications were the Mycetophilidae chapter in the Keys to Insects of the European part of the USSR (Ostroverkhova & Stackelberg 1969) and a monograph of Siberian fungus gnats (Ostroverkhova 1979). She described about 130 new species, one new genus (Neoclastobasis Ostroverkhova, 1970) and one new tribe (Clastobasini Ostroverkhova, 1970) of Sciaroidea and her collection is an important source of primary information about this group in the Palaearctic Region.